Strategi Disabisa Dalam Manajemen Produksi Program Pembelajaran Bagi Calon Content Creator Tunarungu - Josephine Filia Dei (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2024)
Josephine Filia Dei, 210510190078, Communication Management Study Program, Faculty of Communication Sciences, Padjadjaran University. This research is entitled “DisaBisa’s Strategy in Production Management of Learning Program fot Prospective Deaf Content Creators (Qualitative Descriptive Study of DisaBisa’s Strategy in Production Management of Learning Programs for Prospective Deaf Content Creators)” with Dra. Hj. Kismiyati El Karimah M.Si., as the main lecturer, and Dr. Ilham Gemiharto S.Sos., M.Si., as the companion lecturer. This research aims to find out the strategy carried out by DisaBisa in managing the production of learning programs for potential deaf content creators, how the DisaBisa website was established, who are the parties involved in it, what is the production process that the DisaBisa team goes through in presenting learning programs on the website, along with its constraints. This research uses a qualitative method with a descriptive analysis approach, and uses data collection techniques using interviews, documentation, observation, documentation and literature study. The informants for this research are the managers of DisaBisa. Using the Miles & Hubberman analysis technique. The research results show the history of the founding of the DisaBisa website which began with a grant program from the Higher Education. The parties involved include the lecturer team, student team and external parties whose role is to build the website. The production process that the DisaBisa team goes through is divided into the process of creating learning content "Training to be a Content Creator for the Deaf" as well as the process of building and developing the DisaBisa website. During this process, several obstacles were also encountered in terms of time, management's insight into the field of disability, and budget. Through this research, it is hoped that it will be able to produce an overview of the production management process in learning programs for people with disabilities, especially the deaf.